Role of golden jackals (Canis aureus) as natural reservoirs of Dirofilaria spp. in Romania - Ionică, Angela Monica (Parasit Vectors, 2016)
BACKGROUND: Dirofilaria immitis and Dirofilaria repens are mosquito-transmitted zoonotic nematodes, causing heartworm disease and skin lesions, respectively, in carnivores. In Europe, the domestic dog is apparently the main definitive host, but patent infections occur also in other species of carnivores. The rapid spread of the golden jackals (Canis aureus) throughout Europe opens a question of involvement of this species in the sylvatic cycle of pathogens in the colonised territories, including Dirofilaria spp. METHODS: Between January 2014 and May 2015, 54 golden jackals from 18 localities in Romania were examined by full necropsy for the presence of adult filarioid nematodes and blood samples from all animals were screened for the presence of microfilariae of D. immitis, D. repens and Acanthocheilonema reconditum by multiplex PCR DNA amplification. RESULTS: Nematodes morphologically identified as D. immitis were found in 18.52 % of the animals, originating from the southern part of Romania. No D. repens or A. reconditum were found at necropsy. The molecular prevalence in blood samples from the same animals was 9.26 % for D. immitis and 1.85 % for D. repens. All samples were negative by PCR for A. reconditum. CONCLUSION: The relatively high prevalence of Dirofilaria spp. infections in golden jackals from Romania together with the increasing density of the jackal populations highlight their potential role in the transmission of these zoonotic parasites and in the maintenance of natural disease foci.